Framework of knowledge management efficiency in Malaysian engineering consulting firms - Othman, Azlan (2021)
The Malaysian construction industry is one of the backbones to accelerate economic growth. However, in today’s competitive environment, the persistence of engineering and construction organisations depends on knowledge and innovation, which are mainly contributed by knowledge management (KM) practices. Although KM practices improve a company's performance and working efficiencies, the engineering consulting firms still lack systematic methods or reports on its implementation to create, capture, store, share, and reuse a professional's domain knowledge of products, people, and processes. Hence, the aim of the study is to develop a framework of KM practice in engineering consulting firms in the Malaysian construction industry, fulfilled through five research objectives, which are: (1) identifying the main processes of the current KM implementation; (2) determining the challenges of KM efficiency; (3) assessing the critical success factors (CSF) of KM efficiency; (4) examining the relationships of independent variables (namely processes, understanding, challenges, and CSF) and the dependent variable (namely KM efficiency) with the moderation of experience of engineers to understand KM implementation; and (5) developing a framework of KM for engineering consulting firms in the Malaysian construction industry. A literature review was performed to construct a 90-item questionnaire, which has passed the reliability of 0.700 through a pilot study involving 30 participants from the construction industry, hence 202 successful responses were collected from professional engineering consulting firms in the northern region of Peninsular Malaysia. The analysis using the Statistical Package of Social Sciences (IBM SPSS version 23) and Smart Partial Least Squares (Smart PLS version 3.2.9) software shows that: (1) the main processes of current KM are identification, capturing, dissemination, utilisation, sharing, storage, and planning; (2) the challenges of KM efficiency are technological, organisational and individual; (3) CSFs of KM efficiency are organisational, technology, and people; (4) there is a positive relationship between KM processes, understanding, challenges and CSF, and KM efficiency among professional staff working in engineering consulting firms; and (5)the framework of KM for engineering consulting firms in the Malaysian construction industry consists of independent variables of 4 constructs of KM processes, understanding, challenges, and CSF, towards the dependent variable of KM efficiency, which is moderated by experienced consulting engineers. The primary contribution of this study is the development of a framework to improve KM in engineering consulting firms, demonstrating the positive impacts of the four variables namely processes, understanding, challenges, and CSF on KM efficiencies. Moreover,it presented an evidence-based strategy to enhance the growth of consulting business,which will boost the country’s economy. Likewise, key policymakers, including the Construction Industry Development Board could employ the proposed framework to equip the construction industry to realise Organisational Strategic Plan 2021-2025 by the Ministry of Works. This framework is closely aligned with the United Nations Sustainable Development Goals to meet partnership goals worldwide through a knowledge-sharing culture of expertise, technology, and financial resources,especially for developing countries like Malaysia.